2012
DOI: 10.1128/jvi.05909-11
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Norovirus Inhibition and Fucose Mimicry by Citrate

Abstract: Human noroviruses bind with their capsid-protruding domains to histo-blood-group antigens (HBGAs), an interaction thought to direct their entry into cells. Although human noroviruses are the major cause of gastroenteritis outbreaks, development of antivirals has been lacking, mainly because human noroviruses cannot be cultivated. Here we use X-ray crystallography and saturation transfer difference nuclear magnetic resonance (STD NMR) to analyze the interaction of citrate with genogroup II (GII) noroviruses. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 54 publications
3
61
1
Order By: Relevance
“…2E) (13). A similar group of residues in the P domains of noroviruses was shown to bind glycans (30,31). Alternatively, the putative catalytic site may facilitate the escape of DWV virions from endosomes in a manner analogous to the lipase activity present in the N-terminal domain of the capsid protein VP1 from parvoviruses (32).…”
Section: Resultsmentioning
confidence: 98%
“…2E) (13). A similar group of residues in the P domains of noroviruses was shown to bind glycans (30,31). Alternatively, the putative catalytic site may facilitate the escape of DWV virions from endosomes in a manner analogous to the lipase activity present in the N-terminal domain of the capsid protein VP1 from parvoviruses (32).…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, we found that citrate can also occupy the HBGA pocket ( Fig. 1) and might perform as a weak natural inhibitor against HBGAs (23,30), comparably to HMOs.…”
Section: Structural Mimicry Of Hbgas and Hmosmentioning
confidence: 88%
“…Moreover, we recently showed that the GII.4 and GII.10 noroviruses actually have four fucose binding pockets per dimer (21,22). The affinity between norovirus and HBGAs is weak and in the high micromolar range (23), and, based on the number of direct hydrogen bonds and water-mediated interactions, small changes in P domain affinities to HBGAs may exist.…”
Section: Structural Basis For Norovirus Binding To Hbgasmentioning
confidence: 99%
“…Lactose showed no inhibition at any concentration, indicating a lack of binding to the VLPs. Our previous results showed that fucose and HBGA H2 trisaccharide had relatively weak (ϳ0.5 mM) affinities to the GII.10 P domain (20). Therefore, considering that 2=FL and 3FL might also have similar affinities and since mothers' milk contains ϳ1 to 5 mM 2=FL/3FL, these HMOs might compete against HBGA binding.…”
Section: Fig 1 Hmos and Blocking Of Binding Of Norovirus Vlps To Hbgamentioning
confidence: 97%